2018
DOI: 10.1186/s12958-018-0416-0
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone ameliorates palmitic acid-induced cytotoxicity in TM4 Sertoli cells

Abstract: The Sertoli cell is the only somatic cell within the seminiferous tubules, and is vital for testis development and spermatogenesis. Rosiglitazone (RSG) is a member of the thiazolidinedione family and is a peroxisome proliferator-activated receptor-γ (PPARγ) agonist. It has been reported that RSG protects various types of cells from fatty acid-induced damage. However, whether RSG serves a protective role in Sertoli cells against palmitic acid (PA)-induced toxicity remains to be elucidated. Therefore, the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…A previous study found that diet-induced obesity increases Sertoli cell apoptosis and lipotoxicity, accompanied with elevated free fatty acid levels in the testes 29,30 .…”
Section: Discussionmentioning
confidence: 94%
“…A previous study found that diet-induced obesity increases Sertoli cell apoptosis and lipotoxicity, accompanied with elevated free fatty acid levels in the testes 29,30 .…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, overexpression of LRRK2 increased the levels of CPT1A in HepG2 cells ( Figure 4 d). Previous studies indicate that fatty acid induces β-oxidation by increasing CPT1A [ 23 , 45 , 46 ]. Therefore, we analyzed the changes of CPT1A in the LRRK2-overexpressed and control HepG2 cells after treatment with PA at 0, 200, or 400 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown M5 decreased cell-cell junction proteins in spermatogonia stem cells. To further search for the M5 mechanism during spermatogenesis, M5 expression was modi ed in spermatogonia stem cells (C18-4 cell line) (He et al, 2009;Hofmann et al, 2005) and Sertoli cells (TM4 cell line) (Ge et al, 2018). The protein level of M5 in C18-4 cells was decreased by shM5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%